Flourishing and integrative emotion regulation: an SDT perspective - Curren, Randall; Park, Sieun Sienne (Frontiers in Psychology, 2024)
This paper presents a Self-Determination Theory (SDT) perspective on the relationship between human flourishing and emotion regulation. It argues that SDT's organismic approach to motivation, development, and wellness enables it to directly address this relationship, placing emotion regulation within comprehensive conceptions of eudaimonic functioning (i.e., flourishing) and regulation (i.e., self-determination). This is in contrast to the dominant goal-directed process model of emotion regulation, which addresses only limited aspects of well-being, ignores forms of motivation that are essential to flourishing, and blurs the line between emotion regulation and other forms of regulation.